The Impact of Physical Exercises on the Psychomotor Capacities of Middle School Pupils - B. Ghica; M. Onoi; M.-L. Ionescu (Editura Universitatii Transilvania din Brasov, 2023)
The research aims to identify the adolescents' avoidance causes from physical education lessons and to determine the means of improving students' satisfaction with physical education. The present research is of ascertaining - ameliorative type, carried out on a sample of 15 teachers and 180 pupils from secondary classes in the Secondary School "Alexandru Ioan Cuza" and the Secondary School no 10 Bacau, Romania, between March 1, 2022 and June 10, 2022. The methods used in the research included: the analysis of the specialized literature, the diagnosis questionnaire, and the mathematical-statistical method. The main conclusions refer to the identification of the passionate fields and the preferences for the sport of the pupils, the argumentation of the need to introduce in the physical education and sports classes competitive sports games, which, besides the training of some motor qualities, ensure an extremely complex set of psychic sentimental, emotional, volitional and cognitive nature acquisitions.